2012
DOI: 10.1016/j.brs.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of large-scale brain networks by transcranial direct current stimulation evidenced by resting-state functional MRI

Abstract: Background Brain areas interact mutually to perform particular complex brain functions such as memory or language. Furthermore, under resting-state conditions several spatial patterns have been identified that resemble functional systems involved in cognitive functions. Among these, the default-mode network (DMN), which is consistently deactivated during task periods and is related to a variety of cognitive functions, has attracted most attention. In addition, in resting-state conditions some brain areas engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
193
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(216 citation statements)
references
References 60 publications
20
193
2
1
Order By: Relevance
“…This result is consistent with a recent study (Zheng et al, 2011) that reports a positive correlation between the stimulated motor cortex and the contralateral one, supporting a possible coupling of neuroactivity between motor regions (although in our study, the stimulated hemisphere was more strongly activated than the contralateral region). We suppose that the mechanisms responsible for this widespread and bihemispheric anodal effect Pena-Gomez et al, 2011;Polania et al, 2010b) could involve current flowing in subcortical regions such as the thalamus (Bindman et al, 1962), which is the principal subcortical mediator of the TMS-contralateral response (Komssi et al, 2002). A tDCS-induced effect on the cortico-subcortical networks is supported also by recent evidence of a functional coupling increase on the thalamo-cortical circuits following anodal stimulation over the motor cortex (Polania et al, 2012).…”
Section: Tdcs-induced Changes In Cortical Excitabilitymentioning
confidence: 72%
“…This result is consistent with a recent study (Zheng et al, 2011) that reports a positive correlation between the stimulated motor cortex and the contralateral one, supporting a possible coupling of neuroactivity between motor regions (although in our study, the stimulated hemisphere was more strongly activated than the contralateral region). We suppose that the mechanisms responsible for this widespread and bihemispheric anodal effect Pena-Gomez et al, 2011;Polania et al, 2010b) could involve current flowing in subcortical regions such as the thalamus (Bindman et al, 1962), which is the principal subcortical mediator of the TMS-contralateral response (Komssi et al, 2002). A tDCS-induced effect on the cortico-subcortical networks is supported also by recent evidence of a functional coupling increase on the thalamo-cortical circuits following anodal stimulation over the motor cortex (Polania et al, 2012).…”
Section: Tdcs-induced Changes In Cortical Excitabilitymentioning
confidence: 72%
“…Of particular interest will be how tDCS-induced changes in localised connectivity patterns affect large-scale brain dynamics. For example, Sstimulating the motor cortex has been shown to increase functional connectivity within that structure (Polania et al, 2012), and increased connectivity within the default mode network and attention network has been reported from stimulation of the DLPFC (Keeser et al, 2011;Pena-Gomez et al, 2012). The application of graph theory to network organisation has also identified the presence of hubs that have a large number of connections and appear essential for brain communication.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also investigated the effect of tDCS on whole-brain network activity (Polania et al, 2011;Pena-Gomez et al, 2012;Sehm et al, 2013). These studies have A c c e p t e d M a n u s c r i p t Sale et al,19 shown that tDCS has profound yet predictable effects on widespread functional connectivity.…”
Section: Changing the Functional Interplay Between Multiple Networkmentioning
confidence: 99%